General And Specific Considerations Regarding Non-Agricultural Activities In Chișinău District, Republic of Moldova - Ina Mogildea; Ludmila Mogildea; Gheorghe Adrian Zugravu; Maria Magdalena Turek Rahoveanu (Communications of International Proceedings, 2022)
This chapter aims to investigate demographic changes in the population in the Chișinău District, where the threats of the countryside marked by unemployment and the phenomenon of aging are studied. Broadly speaking, in Moldova, the rural landscape is depopulating and not aging. That is why we want to analyze the relationship between the natural demographic balance and the phenomenon of migration during the period 2014-2021. Our study shows that in Chisinau District, the population is lost through migration. No relationship was observed between the demographic type of the rural area and unemployment. Likewise, the Chișinău District is depopulating in general, but its demographic development does not depend on unemployment. However, the rural landscape of the Chișinău District is different. There are some extremely peripheral parts, often lacking a true urban center, where depopulation is the problem. Such territories should be analyzed individually according to local conditions.